Molecular dynamics of Dkk4 modulates Wnt action and regulates meibomian gland development - Sima, Jian; Piao, Yulan; Chen, Yaohui; Schlessinger, David (Development (Cambridge), 2016)
Secreted Dickkopf (Dkk) proteins are major Wnt pathway modulators during organ development. Dkk1 has been widely studied and acts as a general Wnt inhibitor. However, the molecular function of other Dkks remains largely unknown. Here, we show that Dkk4 selectively inhibits a subset of Wnts, but is further inactivated by proteolytic cleavage. Meibomian gland (MG) formation is employed as a model where Dkk4 and its Wnt targets are expressed. Skin-specific expression of Dkk4 arrests MG growth at early germ phase, which is similar to that observed in Eda-ablated Tabby mice. Consistent with transient Dkk4 action, intact Dkk4 inhibits MG extension but the cleaved form progressively increases during MG development with a concomitant upswing in Wnt activity. Furthermore, both Dkk4 and its receptor (and Wnt co-receptor) Lrp6 are direct Eda targets during MG induction. In cell and organotypic cultures, Dkk4 inhibition is eliminated by elevation of Lrp6. Also, Lrp6 upregulation restores MG formation in Tabby mice. Thus, the dynamic state of Dkk4 itself and its interaction with Lrp6 modulates Wnt function during MG development, with a novel limitation of Dkk4 action by proteolytic cleavage.